APHIDS (HEMIPTERA: APHIDIDAE) ASSOCIATED WITH GRASSLANDS OF CENTRAL ALBORZ, IRAN (Acta Entomologica Serbica, 2012)
The aphid fauna associated with various host plants in grassland areas of central Alborz in Iran were studied. The samples were collected from 2002-2010 from different locations  in the southern foothills of  the Alborz Mountains which are a major highland on  the plateau of Iran. Eighty aphid species from 32 genera in association with 168 host plants were collected and identified.  In all, 284 aphid-host plant associations were recorded, 112 of which are new to Iran. Our results showed that grassland areas of central Alborz could be considered as major refugia for aphids from where they migrate to the neighboring cultivated fields. The aphid fauna associated with various host plants in grassland areas of central Alborz in Iran were studied. The samples were collected from 2002-2010 from different locations  in the southern foothills of  the Alborz Mountains which are a major highland on  the plateau of Iran. Eighty aphid species from 32 genera in association with 168 host plants were collected and identified.  In all, 284 aphid-host plant associations were recorded, 112 of which are new to Iran. Our results showed that grassland areas of central Alborz could be considered as major refugia for aphids from where they migrate to the neighboring cultivated fields.